Effect of Media Audio Visual Aid (Video Cassette) Use In Health Promotion on Older People's Level of Knowledge Related to Good Hygiene and Healthy Lifestyle - Esti Dwi Widayanti; Hery Prasetyo; Taat Sumedi (Jurnal LINK, 2014)
Being older is the growth process; healthy ageing requires health promoting behaviors,especially having good hygiene and healthy lifestyle. An audio-visual media aid with video cassette is one of the media in health promotion that can be used to provide knowledge to the older people. The purpose of this study was to determine the effect of media AVA (video Cassette) use in health promotion to the level of knowledge related to good hygiene and healthy lifestyle. This study was a quasiexperimentalresearch with a pre-test and post test with control group design. The design was chosen to measure the difference between before and after the intervention using a control group. The intervention group received health education with AVA media to increase knowledge of good hygiene and healthy lifestyle, whereas the control group received usual health education. A total of 25 older people participated in this study. The results of study showed that after receiving health education with AVAmedia, the intervention group had a significant higher level of knowledge related to good hygiene and healthy lifestyle than the control group (p=0.03). In addition, the level of knowledge related to good hygiene and healthy lifestyle of the intervention group after receiving health education with AVA media also significant higher than that before intervention (p=0.000). Therefore, AVA media can be used as media of health education for the older people to improve knowledge about the clean and healthy lifestyle in the community.